Didactic material adapted for the teaching of Hygiene and Health: Healthy Memory game for students with Autism Spectrum Disorder (ASD) (Research, Society and Development, 2021)
Developing hygiene and health habits in children with Autism Spectrum Disorder (ASD) is challenging because these individuals have persistent inability in communication and social interaction, often added to sensory dysfunctions. This difficulty becomes more evident when school age arrives, where the learning of socially constructed concepts is necessary, precisely because they need interaction with their peers. In this sense, the content covered in this work is related to the concepts of Hygiene and Health worked in a playful way through the Healthy Memory game to support the learning of students with ASD. Autistic students with difficulties in verbal communication, enrolled from Kindergarten to the 4th year of Elementary School, and the mediators of the multifunctional resource rooms participated in this research. The present study was characterized as qualitative, as it evaluated the behavior, speeches and experiences of the subjects involved. The data collection instrument used was direct observation carried out by the professor-researcher. To use the game, students needed to pair twenty cards, ten with drawings where there were health-related risk situations and another ten with good hygiene habits. The results obtained showed: i) that the number of smaller pieces favored understanding; ii) that there was a need to use color contrast, such as yellow and red, in addition to simplifying the images and, iii) that the game worked as a verification of learning for students who had previous experiences with hygiene material and/or performed self-care with autonomy. These data reinforced the hypothesis of the game as communication for learning basic activities of daily living (BADL) and its relationship with health, so essential for autistic people with low verbalization functionality. Thus, we can indicate the use of the game in its entirety or in a flexible way, with a reduction in the number of cards or selection of those indicated for the target audience for the construction of symbolic thinking on the theme of Hygiene and Health.